Responses of roots and rhizosphere of female papaya to the exogenous application of GA3 - Zhou, Yongmei; Pang, Ziqin; Jia, Haifeng; Yuan, Zhaonian; Ming, Ray (BMC plant biology, 2023)
Exogenous GAs have an indeterminate effect on root development. Our current study used female papaya to reveal how the roots and rhizosphere respond to the exogenous application of GA 3 by investigating the transcriptome profile in roots, metabolic profile and microbial community in both roots and rhizosphere of GA 3 -treated and control female papaya. The results demonstrated that exogenous GA 3 treatment enhanced female papaya lateral root development, which gave plants physical advantages of water and nutrient uptake. In addition, it was likely that GA 3 spraying in papaya shoot apices increased the level of auxin, which was transported to roots by CpPIN1, where auxin upregulated CpLBD16 and repressed CpBP to promote the lateral root initiation and development. In papaya roots, corresponding transporters ( CpTMT3 , CpNRT1:2 , CpPHT1;4 , CpINT2 , CpCOPT2 , CpABCB11 , CpNIP4;1 ) were upregulated and excretion transporters were downregulated such as CpNAXT1 for water and nutrients uptake with exogenous GA 3 application. Moreover, in GA 3 -treated papaya roots, CpALS3 and CpMYB62 were downregulated, indicating a stronger abiotic resistance to aluminum toxic and phosphate starvation. On the other hand, BRs and JAs, which involve in defense responses, were enriched in the roots and rhizosphere of GA 3 -treated papayas. The upregulation of the two hormones might result in the reduction of pathogens in roots and rhizosphere such as Colletotrichum and Verticillium . GA 3 -treated female papaya increased the abundance of beneficial bacteria species including Mycobacterium , Mitsuaria , and Actinophytocola , but decreased that of the genera Candidatus and Bryobacter for that it required less nitrate. Overall, the roots and rhizosphere of female papaya positively respond to exogenous application of GA 3 to promote development and stress tolerance. Treatment of female papaya with GA3 might result in the promotion of lateral root formation and development by upregulating CpLBD16 and downregulating CpBP . GA 3 -treated papaya roots exhibited feedback control of brassinolide and jasmonate signaling in root development and defense. These findings revealed complex response to a growth hormone treatment in papaya roots and rhizosphere and will lead to investigations on the impact of other plant hormones on belowground development in papaya.